Semantic modifications of English used by Manuel E. Arguilla in his short stories to suit native material and culture - Linab, Clara
The semantic modification of English in the short stories of Manuel E. Arguilla was described and analyzed to determine how English, a foreign language behaves in its contact with native characteristics, scenes, and situations and how it is modified to suit Philippine material and culture. The description and analysis of the semantic modifications of English in the sixteen short stories discovered some discerning devices used by Manual E. Arquilla to achieve congruity between the foreign language and the native material and culture. Such devices are the following : 1. Transliteration. When the story material is deeply rustic, Arguilla writes native nuances and expressions in English words whose meanings correspond to the semantics of the native language. This device is used when situations are so embedded by native psychology and culture that no true English expressions can adequately express the meaning intended in the original. 2. Use of semantic equivalent. When the material defies transliteration, Arguilla uses English words and expressions that are not transliterations but which do project an English parallel to the flavor of the material.3. Tranference. When the story material is heavily tinged with Western influence as in the city stories, The English language is made to function as it is; there is a transference that gives the impression of being equational, a transference from the English language as used in its native soil to the English language used in a foreign soil that has imbedded its ways and culture. 4. Other forms of semantic modification. Other forms of semantic modification are observed in the author's use of native objects and symbols, thus giving the sentences, meaning that have a reality in the native culture. Still considered a modification of some sort, is the use of Philippine names and honorifics, much of which is found in the barrio stories. The result could be summarized as follows: For stories that are deeply rustic, Manuel E. Arguilla employed three alternatives with which to modify the language - transliteration, use of semantic equivalent, snd use of native names and honorifics; For stories that are deeply urban and tinged with western influence, Arguilla used transference.